2021
DOI: 10.1038/s41598-021-91424-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of plant labile carbohydrates and nitrogen on wheat-aphid relations 

Abstract: Interactions between plants and herbivores are key drivers of evolution and ecosystem complexity. We investigated the role of plant labile carbohydrates and nitrogen on wheat-aphid relations in a 22 factorial combining [CO2] and nitrogen supply. We measured life history traits (assay 1) and feeding behaviour (assay 2) of bird-cherry oat aphid (Rhopalosiphum padi L.) and English grain aphid (Sitobion avenae F.) forced to feed on single leaf laminae, and reproduction of R. padi in a setting where insects moved f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…However, the response of carbohydrate reserves to neighbour lacked symmetryconcentration of water-soluble carbohydrates increased in Halberd with Scepter neighbour but did not reduce in the same proportion in Scepter with Halberd neighbour. The reason for this lack of symmetry is unknown; it has been speculated that high concentration of water-soluble carbohydrates could play an osmotic role and increase in response to selection for tolerance to aphids (Sadras et al, 2020(Sadras et al, , 2021.…”
Section: Older Taller Cultivars Outcompeted Newer Shorter Cultivars F...mentioning
confidence: 99%
“…However, the response of carbohydrate reserves to neighbour lacked symmetryconcentration of water-soluble carbohydrates increased in Halberd with Scepter neighbour but did not reduce in the same proportion in Scepter with Halberd neighbour. The reason for this lack of symmetry is unknown; it has been speculated that high concentration of water-soluble carbohydrates could play an osmotic role and increase in response to selection for tolerance to aphids (Sadras et al, 2020(Sadras et al, , 2021.…”
Section: Older Taller Cultivars Outcompeted Newer Shorter Cultivars F...mentioning
confidence: 99%
“…Saturated vs. unsaturated lipid ratios play a crucial role in plant survival and stress tolerance [ 60 ]. In this experimental setting, we found that high levels of CO 2 increased fructose and glucose concentrations, which are essential to buffer the growth requirement of wheat, and play an osmotic role in plant resistance to aphids [ 5 ]. Kanobe et al [ 56 ] concluded that aphids reduced the levels of PUFAs in the leaves and seeds of soybean plants.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental procedure is fully explained elsewhere [ 5 ]. Briefly, wheat (cv Pedrosa) plants were grown in 9 cm × 9 cm × 10 cm pots with vermiculite (Asfaltex S.A., Barcelona, Spain) in growth chambers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations